2004
DOI: 10.1289/ehp.6581
|View full text |Cite
|
Sign up to set email alerts
|

Association between hemochromatosis genotype and lead exposure among elderly men: the normative aging study.

Abstract: Because body iron burden is inversely associated with lead absorption, genes associated with hemochromatosis may modify body lead burden. Our objective was to determine whether the C282Y and/or H63D hemochromatosis gene (HFE) is associated with body lead burden. Patella and tibia lead levels were measured by K X-ray fluorescence in subjects from the Normative Aging Study. DNA samples were genotyped for C282Y and H63D using polymerase chain reaction/restriction fragment length polymorphism (PCR/RFLP). A series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
50
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 40 publications
7
50
2
Order By: Relevance
“…The present findings are consistent with our previous report that HFE variants were associated with lower levels of blood lead and bone lead in the same NAS cohort. 18 The proposed mechanism for this effect was that HFE variants indirectly reduce lead exposure. Subjects with HFE variants are at lower risk for iron deficiency, 33,34 and the overall increase in body iron stores among people with HFE variants may result in reduced expression of proteins that regulate divalent metal absorption, thus reducing the body burden of lead.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present findings are consistent with our previous report that HFE variants were associated with lower levels of blood lead and bone lead in the same NAS cohort. 18 The proposed mechanism for this effect was that HFE variants indirectly reduce lead exposure. Subjects with HFE variants are at lower risk for iron deficiency, 33,34 and the overall increase in body iron stores among people with HFE variants may result in reduced expression of proteins that regulate divalent metal absorption, thus reducing the body burden of lead.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Because iron stores are inversely associated with the gastrointestinal absorption of multiple potentially toxic metals (lead, cadmium, manganese, copper, and cobalt), 16,17 HFE variants may modify the effect of particulate transition metals, and in previous studies, HFE variants were associated with lower blood and bone levels of lead, a toxic divalent metal. 18 We hypothesized that the HFE genetic polymorphism modifies the effect of ambient PM 2.5 on cardiac autonomic function. We previously found a significant association between PM 2.5 and decreased heart rate variability (HRV), a marker of cardiac autonomic dysfunction and a predictor of sudden cardiac death and arrhythmia, 19,20 among older men.…”
mentioning
confidence: 99%
“…The gene codes for a protein designated HFE and has two variants: C282Y and H63D. Wright et al (2004) studied 730 men from the Normative Aging Study and found that the presence of a hemochromatosis variant, either C282Y or H63D, predicted lower bone and blood lead concentration. Based on the fact that iron…”
Section: Health Effectsmentioning
confidence: 99%
“…status is inversely related to lead absorption, Wright et al (2004) hypothesized that the results may be secondary to increased iron stores among HFE variant carriers leading to decreased lead absorption in the gastrointestinal tract. Previously, Barton et al (1994) found that homozygous individuals who suffered from hemochromatosis had higher PbB than individuals who did not have the gene.…”
Section: Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation